Distillation of ethanol in the bioethanol production - Boiko, Petro; Bondar, Nikolai; Kuts, Anatoly (My University, 2017)
В работе рассматриваются технологические аспекти выделения этилового спирта из бражки при производстве топливного спирта. The paper considers technological aspects extraction of alcohol from mash in the production of fuel alcohol.
Keywords: бражка; топливный спирт; дистилляция; fuel alcohol; distillation; mash; кафедра біотехнології продуктів бродіння і виноробства